PENERAPAN MODEL PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 6 PRAYA TIMUR - Dika Rahman Efendi; Bq. Azmi Sukroyanti (Lensa: Jurnal Kependidikan Fisika, 2014)
The lack of skill in grade VIII students is very worrying. Learning activities are still teacher-centered, donated by conventional methods, and methods that are not appropriate so that students are not active during the learning and impact on the low achievement of learning. Therefore, to solve the problem in this research used the application of science learning model of community technology to improve learning achievement. This study aims to improve student achievement. This classroom action research was conducted in 2 cycles; data collected using observation sheets, 'process skill' tests and evaluation tests. Data has been quantitatively analyzed. The subjects of this study are all classes VIII-A at SMP Negeri 6 east praya, amounting to 28 students. The results showed that the average of learning outcomes in cycle I was 34, 9 with 10, 7% classical completeness. In cycle II has increased average to 67, 5 with classical completeness 85, 7%. Skills of students' science processes increase from cycle I to II. This research can be concluded that in the application of learning model of 'community technology science' has been able to improve students' science process skill.